Developing two tests for the skills of the forehand and backhand badminton stroke for the advanced category. - Faydullah, Asst.Prof.Dr.Muhammad Jalal (Sulaimani Journal for Humanities, 2026)
Badminton is a comprehensive sport, relying on the fundamental requirements of any other sport, such as skill, physical, tactical, psychological, mental, and body composition. It is characterized by fluctuating tension and effort from moment to moment. "Badminton, like tennis, is a fast-paced game with short-term exertion followed by a short recovery phase." This research aims to develop and standardize two tests for the forehand and backhand strokes in badminton for advanced players, and to establish standardized scores and levels for these tests. The sample consisted of players from clubs participating in the 2024 Iraq Cup in the advanced category, and the study period ran from June 3, 2024, to January 4, 2025. A descriptive survey methodology was used to achieve the research objectives. The research population comprised 58 players from clubs participating in the 2024 Iraq Open Badminton Cup in the advanced category. The research sample consisted of 54 players. The researcher developed two tests: one for the accuracy of the forehand and backhand strokes. The researcher concluded that skill tests for the forehand and backhand strokes were developed to reflect changes in badminton, and standardized scores and levels were established for the tests. The sample's performance in the forehand and backhand stroke tests varied, ranging from very good to good, average, acceptable, and weak. The researcher recommends that coaches and specialists adopt these two tests to assess the skill levels of advanced players and assist them in developing their players. The researcher also recommends that the established scores and standardized levels be used as a means of objective evaluation.
Keywords: Front diversion shot; back diversion shot